SECURITY OF IINFORMATION RESOURCES IN UNIVERSITY LIBRARIES: A CASE STUDY OF SOUTH-EAST NIGERIA - Agbakwa, Maryjane Amarachi; Ogunbodede, Kolawole Francis (Indonesian Journal of Library and Information Science, 2025)
This study analyzed the security of information resources in federal university libraries in south-east Nigeria. The study used a descriptive survey, and the population comprised 172 librarians from five federal university libraries in south-east. Given the small size of the target population, a census sampling technique was applied to sample all the 172 librarians. The data was collected using an online questionnaire. The survey was administered to 172 librarians, with 135 of them returning it, thus, the response rate was 73%. The mean and standard deviation were calculated using SPSS version 29 after the data had been analyzed with frequency counts and simple percentages. The findings revealed that physical access control, ID cards and access authorization, fire prevention and suppression equipment, CCTV cameras, the use of security guards, registration at the gate, and alarm systems were some of the security measures that were implemented, with a low level of implementation of 3m exist detection systems and RFID technology. The findings also show that librarians have moderate-level awareness about security protocols with significant limitations in staff development programs, regular training, and the communication of best security practices. Librarians encounter significant challenges in securing information resources, such as inadequate funding, lack of trained personnel to implement security protocols, cyber threats such as hacking or malware, outdated or malfunctioning security equipment, and theft/vandalism of physical resources. Based on the findings, the researchers recommended, among other things, that university libraries in south-east Nigeria require greater financial support to purchase modern security equipment, maintain their infrastructure and train their security personnel.